Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/plants11070994
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Profile and Anticancer Activity of Anthemis tinctoria and Angelica sylvestris Used in Estonian Ethnomedicine

Abstract: The aerial parts of Anthemis tinctoria L. and Angelica sylvestris L. and the roots of A. sylvestris have been used as traditional anticancer remedies in Estonian ethnomedicine. The aim of this study was to investigate content of essential oils (by gas chromatography) and polyphenolic compounds (using two different methods of high performance liquid chromatography–mass spectrometry (HPLC–MS)) of both plant species, as well as the in vitro anti-cancer effects of their essential oils and methanolic extracts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Plants are a natural source of active compounds, phytochemicals, many of which with favourable bioactivity for humans. Analytical investigation allows for the determination of the phytochemical composition and confirmation of specific therapeutic properties of the plants already acknowledged for their potential by ethnomedicine [ 1 , 2 , 3 , 4 , 5 ]. The Galium L. genus, comprising about 667 species found worldwide, over a third of which can be found in Europe, includes several species that have been used in traditional medicine to alleviate a variety of ailments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are a natural source of active compounds, phytochemicals, many of which with favourable bioactivity for humans. Analytical investigation allows for the determination of the phytochemical composition and confirmation of specific therapeutic properties of the plants already acknowledged for their potential by ethnomedicine [ 1 , 2 , 3 , 4 , 5 ]. The Galium L. genus, comprising about 667 species found worldwide, over a third of which can be found in Europe, includes several species that have been used in traditional medicine to alleviate a variety of ailments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through GC-MS, the contents abundant in N. mirandaleaf-acetone were detected and identified (Table 3). We found that the top four contents, plumbagin (28.52%) [57][58][59][60], lupenone (11.45%) [69][70][71], palmitic acid (5.49%) [72][73][74], and stigmast-5-en-3-ol (5.06%) [75], especially plumbagin and lupenone, are anticancer compounds. This might be why N. miranda-leaf-acetone possesses strong cytotoxic activities.…”
Section: Discussionmentioning
confidence: 92%
“…Purification and fractionation of the extract isolated from G. hederacea resulted in three fractions: 20% fraction, 60% fraction, and 85% fraction. Major components of the above-mentioned preparations were tentatively identified and classified on the basis of their MS and UV spectra, chemical analysis, and literature data [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] ( Table 1 ). For example, the total concentration of phenolic acids in the extract was 177.64 mg/g, while the total flavonoid content was 115.8 mg/g ( Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%